Water Contamination by Nitrates and its Thyroid Disruptive Action. Bioassay on Xenopus Laevis (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: endocrine disruptors - xenopus - groundwater - nitrates #x2013; thyroid